2011
DOI: 10.1128/aem.02643-10
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Rapid Evolution of theluxR-luxIIntergenic Region to the Diverse Bioluminescence Outputs ofVibrio fischeriStrains Isolated from Different Environments

Abstract: Vibrio fischeri serves as a valuable model of bacterial bioluminescence, its regulation, and its functional significance. Light output varies more than 10,000-fold in wild-type isolates from different environments, yet dim and bright strains have similar organization of the light-producing lux genes, with the activator-encoding luxR divergently transcribed from luxICDABEG. By comparing the genomes of bright strain MJ11 and the dimmer ES114, we found that the lux region has diverged more than most shared orthol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 70 publications
2
35
1
Order By: Relevance
“…Other researchers have made great strides in dissecting the structure and function of LuxN, and we believe that comparative analyses including AinR will be enlightening. Similarly, we are intrigued by the divergence of AinR between V. fischeri isolates from different environments (43), and further investigation could elucidate selective pressures on AinS/ AinR for V. fischeri in different hosts. Finally, we are interested in the regulatory control of AinS/AinR expression, and our results have opened new research avenues, particularly with respect to our discovery of LuxR-mediated regulation and the potential for posttranscriptional control.…”
Section: Figmentioning
confidence: 99%
“…Other researchers have made great strides in dissecting the structure and function of LuxN, and we believe that comparative analyses including AinR will be enlightening. Similarly, we are intrigued by the divergence of AinR between V. fischeri isolates from different environments (43), and further investigation could elucidate selective pressures on AinS/ AinR for V. fischeri in different hosts. Finally, we are interested in the regulatory control of AinS/AinR expression, and our results have opened new research avenues, particularly with respect to our discovery of LuxR-mediated regulation and the potential for posttranscriptional control.…”
Section: Figmentioning
confidence: 99%
“…Interestingly, one clade, referred to as group A strains, exhibits competitive dominance when competed against non-group A strains in colonization experiments with juvenile squid (17). Among V. fischeri strains, the luxIR intergenic region was also shown to be hypervariable and to contribute to the bioluminescence profile of each strain, suggesting that bioluminescence and its regulation are under selection (18,19). How such V. fischeri strain diversity develops within the squid light organ is unclear.…”
mentioning
confidence: 99%
“…3, 4, and 5). The intergenic lux region has diverged significantly between ES114, MJ-1, and other V. fischeri strains, and while a putative CRP binding site is evident in the same location in a variety of strains, the exact sequence of the site does vary (53). The sequence revealed in CRP footprinting analyses of V. fischeri ATCC 7744 DNA by Shadel et al (26) aligns with the ES114 sequence used in our binding studies (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…The sequence revealed in CRP footprinting analyses of V. fischeri ATCC 7744 DNA by Shadel et al (26) aligns with the ES114 sequence used in our binding studies (Fig. 5), although there are several differences in the sequences, particularly in the variable central region of the binding site (53). In addition to demonstrating binding, using a transgenic E. coli system we found that the effect of CRP on luxR requires only the CRP-activating region I, consistent with this effect being mediated by a class I-type promoter interaction.…”
Section: Discussionmentioning
confidence: 99%